Pairwise almost Lindelof bitopological spaces II - Kilicman, Adem; Salleh, Zabidin (Universiti Putra Malaysia Press, 2007)
In this paper we continuation to study the pairwise almost Lindelöf subspaces and subsets,investigate some of their characterizations and obtain some new results.